Gamma Irradiation Technology Preserves Food Quality And Introduces Nuclear Energy’s Important Role In Food Production To Indonesian Society Effectively - Salam, Arham; Kusumawardani, Adelia Putri; Rahman, Aulia; Nur, Wahyuna (Pinisi: Physics Journal, 2025)
Food preservation is a crucial aspect in maintaining the quality, safety, and nutritional value of products, particularly in Indonesia with its rich diversity of food resources. Conventional methods such as drying, salting, and freezing are still dominant but have limitations in preventing food spoilage caused by microbiological and environmental factors. One emerging innovation in modern preservation technology is the use of gamma irradiation. This technology effectively eliminates pathogenic microorganisms without damaging the physical and chemical quality of food products. This literature study aims to understand the working mechanism of gamma irradiation, its impact on food, and its role in enhancing food production in Indonesia. Gamma irradiation uses radiation from radioactive isotopes such as Cobalt-60 to damage microbial DNA, thereby extending product shelf life. The technology is considered safe, leaves no residues, is energy-efficient, and environmentally friendly. However, its application in Indonesia remains limited due to a lack of public awareness and persistent negative stigma surrounding nuclear technology. Public education is key to increasing societal acceptance of food irradiation. With proper implementation, gamma irradiation technology holds significant potential in reducing food waste, enhancing food safety, and supporting national food security.